Pragmatic Approach to Hepatocellular Carcinoma Diagnosis in High-Incidence, Resource-Limited Settings in Africa - Gregory D. Kirk; Sara Nsibirwa; Jim K. Aizire; Redeat L. Assefa; Antonio Bandala-Jacques; Jackson Orem; Tongai Maponga; Moussa Seydi; Gilles Wandeler; Amir Mohareb; David L. Thomas; Fred Okuku; et al. (JCO Global Oncology)
PURPOSEHepatocellular carcinoma (HCC) is common and deadly in sub-Saharan Africa, where advanced imaging techniques, such as computerized tomography and magnetic resonance imaging, are scarce. The purpose of this study was to develop a pragmatic HCC diagnostic strategy for such settings.METHODSWe evaluated standardized protocol-collected data on clinical, ultrasonographic, biochemical, and pathological criteria in a multisite study of 649 suspected HCC cases in Uganda. Participants underwent standardized interviews, clinical assessments, and ultrasound examinations by trained staff with alpha-fetoprotein (AFP) testing at a central laboratory, and pathology was obtained for selected participants. Concordance analysis and percentage-confirmed yield using different HCC case definitions were performed, with survival follow-up as a validation measure.RESULTSThe median age was 45 years, 68% were male, and 45% had chronic hepatitis B infection. Ultrasonographic, biochemical (AFP), and pathological definitions confirmed 91%, 57%, and 17% of clinically defined HCC cases, respectively. The median survival after diagnosis was 46 days. An integrated HCC case definition that combined clinical criteria with one confirmatory test increased the percentage-confirmed yield by 3.7% (ultrasonographic), 37.7% (biochemical), and 77.7% (pathologic) over the clinical definition alone. Yield from AFP or pathology beyond ultrasound was minimal. Survival did not differ appreciably by HCC case definition. This integrated HCC case definition maintained diagnostic rigor while maximizing yield.CONCLUSIONWe propose an integrated HCC case definition as a pragmatic, resource-adaptable approach for clinical diagnosis and research in sub-Saharan Africa. This definition can be readily implemented and can support regional collaborative efforts to develop novel diagnostics and improved treatments to ameliorate the heavy HCC burden.